2004
DOI: 10.1096/fj.04-2146fje
|View full text |Cite
|
Sign up to set email alerts
|

Red wine polyphenols‐induced, endothelium‐dependent NO‐mediated relaxation is due to the redox‐sensitive PI3‐kinase/Akt‐dependent phosphorylation of endothelial NO‐synthase in the isolated porcine coronary artery

Abstract: An enhanced endothelial formation of nitric oxide (NO) by red wine polyphenolic compounds (RWPs) has been involved in the protective effect of chronic intake of red wine on coronary diseases. However, the mechanism underlying the activation of endothelial NO synthase (eNOS) remains unclear. In the presence of indomethacin and charybdotoxin plus apamin to prevent the formation of prostanoids and endothelium-derived hyperpolarizing factor, respectively, RWPs caused pronounced endothelium-dependent relaxations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
174
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(186 citation statements)
references
References 61 publications
10
174
0
2
Order By: Relevance
“…The inhibition of EDHF-mediated responses with charybdotoxin plus apamin did not affect relaxations to ALF. In contrast to red wine extract (Ndiaye et al 2005), the relaxation to ALF persisted in the presence of the combination L-NA, charybdotoxin and apamin on pig coronary artery. The persistent relaxation to ALF was not due to the formation of relaxing prostanoids; since all experiments were performed in the presence of indomethacin.…”
Section: Discussionmentioning
confidence: 66%
“…The inhibition of EDHF-mediated responses with charybdotoxin plus apamin did not affect relaxations to ALF. In contrast to red wine extract (Ndiaye et al 2005), the relaxation to ALF persisted in the presence of the combination L-NA, charybdotoxin and apamin on pig coronary artery. The persistent relaxation to ALF was not due to the formation of relaxing prostanoids; since all experiments were performed in the presence of indomethacin.…”
Section: Discussionmentioning
confidence: 66%
“…3), although this acute activation of eNOS is consistent with a previous report showing that RV induced endothelial NO production. [34][35][36] The effect of RV on the endothelium resembles that of clonidine, an α 2 -adrenergic receptor agonist. In our previous study, we reported that the clonidine-induced relaxation response in DM mice decreased through the inactivation of the Akt/eNOS signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine is mainly dependent on an increase in intracellular free calcium concentration in endothelial cells. RWPs have been shown to induce arterial relaxations, mainly through the redox-sensitive activation of the PI3-kinase pathway (Ndiaye et al, 2004(Ndiaye et al, , 2005. Therefore, we sought to verify whether angiotensin II is able to discriminate the two distinct endothelial intracellular pathways in response to the two stimuli, acetylcholine and RWPs.…”
mentioning
confidence: 99%